EFFECTS OF EXTREMELY LOW FREQUENCY ELECTROMAGNETIC FIELD AND MECHANICAL VIBRATION ON SPECIFIC ELECTRICAL CONDUCTIVITY OF DISTILLED WATER AND PHYSIOLOGICAL SOLUTIONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
In present work the study of frequency-dependent effects of extremely low frequency electromagnetic field (ELF–EMF) and mechanical vibration (MV) on specific electrical conductivity (SEC) of distilled water (DW) and physiological solutions (PS) is described. The purpose of this study was to find out the frequency windows and demonstrate the dependency of these physical factors’ effect on the environmental conditions. With this aim frequency-dependent (1–9 Hz) effect of ELF–EMF and MV (1 h) on SEC of DW and PS in light and normal background radiation (NBGR) has been investigated. As the “windows” have been observed only at 4 and 8 Hz the next experiments have been performed at this frequency. The experiments were carried out in the following media: in light ($ E_v=500–550~lux$ ) and NBGR, in dark and NBGR (in wooden box), in dark and low background radiation (in lead box, $R
Keywords: distilled water; physiological solutions; specific electrical conductivity; xtremely low frequency electromagnetic field; mechanical vibration